2015
DOI: 10.11002/kjfp.2015.22.5.758
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lactic acid bacteria on changes of aflatoxin levels during kimchi fermentation

Abstract: Red pepper powder sensitive to aflatoxins contamination is major ingredients of kimchi. This study was conducted to investigate the effect of lactic acid bacteria (LAB) on the changes in aflatoxin levels during kimchi fermentation. Baechu kimchi was contaminated with aflatoxins (B1, B2, G1, and G2) and inoculated with LAB (Lactobacillus plantarum and Leuconostoc mesenteroides), and the following characteristics were investigated for 8 weeks: pH, titratable acidity, salinity, microbial properties, and aflatoxin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Cheon et al. () reported that coliforms in kimchi increased after 2 weeks of storage at 4°C. Knarreborg, Miquel, Granli, and Jensen () reported that lactic acid‐induced growth of coliforms at pH 5.5, but at pH 4.5, it could reduce the population of coliforms.…”
Section: Resultsmentioning
confidence: 99%
“…Cheon et al. () reported that coliforms in kimchi increased after 2 weeks of storage at 4°C. Knarreborg, Miquel, Granli, and Jensen () reported that lactic acid‐induced growth of coliforms at pH 5.5, but at pH 4.5, it could reduce the population of coliforms.…”
Section: Resultsmentioning
confidence: 99%
“…There is no research on the mycotoxins contained in kimchi. However, since the main ingredient of kimchi is red pepper powder that is sensitive to mycotoxins contamination [29], the possibility of the presence of mycotoxins in kimchi cannot be excluded. Kimchi can be considered generally safe because it has been consumed safely for a long time.…”
Section: Discussionmentioning
confidence: 99%